A Grammar of the Hurrian Language - Bush, Frederic William
ergänze; University Microfilms Order No. 64-12, 852; Microfilm: $5.70; Xerography $20.30; Dissertation Abstracts 25/8 (Ann Arbor, Mich., Febr. 1965) 4695-4696; Linguistics 20 (The Hague 1966) 88-89.